„Rzeczy warszawskie” – nowa odsłona Muzeum Warszawy - Markowska, Anna (Artium Quaestiones, 2019)
A radical reconstruction of the exposition layout at the Museum of the City of Warsaw, connected with the general reconstruction of the facilities and retirement of its longtime director, Janusz Durko (1951-2003), resulted in 2017 in opening a new permanent exposition called Things from Warsaw. The exposition consists of 21 cabinets containing 8 000 items selected out of 300 000 included in the museum holdings (e. g., Cabinet of Warsaw Monuments, Cabinet of Warsaw Silver and Plate Tableware, Cabinet of the Warsaw Sirens, Cabinet of Postcards, Cabinet of Souvenirs, Cabinet of Shrines). The main criterion was the materiality and authenticity of particular items, which resulted in the absence of multimedia presentations and suggested “appropriate” narratives. The main curator of the exposition is Jarosław Trybuś, art historian and curator rewarded with the Golden Lion at the Venice Biennale in 2008. His team followed an idea of Bjørnar Olsen that due to various conceptualizations the material world studied by the humanities has been so dematerialized that we can hardly believe our eyes. Thus the features of the exposition – sincerity, seriousness, and modesty – suggest a new approach to the city’s history through experiencing the reality of things treated not so much as “witnesses,” but rather as “actors” of the past events. This turn to materiality stems from the hope to come close to the things without the mediation of words imposing predictable interpretations in advance. In other words, the exposition is a kind of lesson in openness, multidirectional reading, and the de-ideologization of history. The Things from Warsawexhibition has been analyzed in reference to three criteria: openness to the “other,” creating a vision of the future, and the inspiring power of imagination.